PENGARUH PEMBERIAN INFUS HANGAT TERHADAP STABILITAS SUHU TUBUH PADA PASIEN POST OPERASI GENERAL ANESTESI DI RECOVERY ROOM RSU KARSA HUSADA BATU - Shabirina Awwaliyah; Moh. Zainol Rachman; Naya Ernawati (Jurnal Keperawatan Terapan, 2020)
Hypothermia is a serious general complication of surgery and anesthesia which can carry out various complications. The action to overcome this problem is the administration of heating measures, one of which is by warm infusion. The aim of this study was to determine the effect of warm infusion on body temperature stability in postoperative general anesthesia patients. The research method used was a pre experimental one group without control with a pretest posttest study. Respondents of this study were postoperative patients with general anesthesia. The population of this study was post operative patients under general anesthesia. The sampling in this study was purposive sampling. The number of samples in this study was 17. Respondents received 30 degrees Celsius warming fluid infusion. The analysis in this study used a comparative test paired t test with the result of P value 0,000. The P value shows a significant effect between giving warm infusions and body temperature stability. Based on descriptive statistical analysis, 76,4 percent of respondents achieved normothermia in the 35th minute. In the 60th minute, all respondents were in a normothermic state. Suggestions for further research to conduct research with more sample sizes. Keywords: Warm Infusion, General Anesthesia, Body Temperature